Applications of atomic-resolution HAADF-STEM and EDS-STEM characterization of light alloys - Nie, Jian-Feng (IOP conference series. Materials Science and Engineering, 2017)
Precipitation-hardened aluminium and magnesium alloys often contain a uniform distribution of plate-shaped precipitates of intermediate or equilibrium phases that form on rational planes of the matrix phase. Micro-alloying additions can change the identity and/or distribution of these precipitate plates, but the precise roles of the micro-alloying elements in the formation of such precipitate plates are still a subject of debate. A key reason for this is the lack of direct experimental observation of the details of the distribution/segregation of these elements in and surrounding precipitates from conventional transmission electron microscopy. While the advent of high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) provides much more information at the atomic-scale, there is still a need for performing atomic-resolution chemical mapping using advanced STEM techniques, such as energy-dispersive X-ray spectroscopy (EDS-STEM) and/or electron energy-loss spectroscopy (EELS-STEM), if the precise roles of the micro-alloying elements are to be revealed.